The Law of one price in Scandinavian Duty-Free Stores: A Report - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
A report written on Asplund, M, and Friberg, Richard (2001). "The Law of One Price in Scandinavian Duty-Free Stores." American Economic Association, vol. 91(4), pages 1072-1083, September.
Keywords: A1; 330; law of one price